Determinasi Kualitas Laba Terhadap Perusahaan LQ45 - Mutiara Sukmadyan Putri; Yovita Ariani (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the partial and simultaneous effects of corporate governance, intellectual capital, and company size on earnings quality. The population in this study consists of LQ45 index companies listed in 2023 on the Indonesia Stock Exchange (IDX) with a research period from 2020 to 2023. The sample was determined using purposive sampling and obtained a sample of 26 companies. This study uses analytical techniques such as descriptive statistics, panel data linear regression model estimation, and hypothesis testing. The research hypothesis testing uses multiple regression analysis using Eviews 13. The results of this study indicate that the variables of corporate governance, intellectual capital, and firm size simultaneously affect earnings quality. Partially, corporate governance and intellectual capital do not affect earnings quality because both can be formalities or merely potential if they are not followed by the implementation of effective internal control and resource management, so that the profits generated do not reflect the actual economic condition of the company. In addition, firm size affects earnings quality because large companies tend to generate earnings quality because they are under strict supervision and are able to ensure that recognized sales actually generate operating cash flow.